Unveiling the mineral resources and structural patterns in the Middle Benue Trough: a comprehensive exploration using airborne magnetic and radiometric data - Stephen E. Ekwok; Anthony M. George; Asuquo A. Omori; Kamal Abdelrahman; Samuel I. Ugar; Peter Andráš; Morod I. Morphy; Anthony E. Akpan; Ahmed M. Eldosouky (Geocarto International)
The Middle Benue Trough (MBT) in Northcentral Nigeria is a geologically significant area with vast mineral resource potential. Employing airborne magnetic and radiometric data, this study utilized the Centre for Exploration Targeting on enhanced total magnetic intensity data to reveal geologic structures, lithological units and mineralization zones. Lineaments predominantly trended in NE-SW direction, with noteworthy orientations in NNE-SSW and E-W. Radiometric anomalies correlated with distinct lithological units, pinpointing granitic gneiss, alluvium, shale, siltstone and sandstone. A magnetically concentrated and potassium-rich area indicated potential polymetallic-magnetic mineralization. The 2D model illustrated igneous intrusions influencing prevalent geologic structures, such as sediment baking and doming. Thorough analysis, including source parameter imaging, standard Euler deconvolution and 2D forward modelling, revealed sediment thicknesses below 1500 m. This research enhances understanding of the MBT’s geological features, offering valuable insights for mineral exploration and resource assessment in the region.